(3GdhSjW aj JaSjQ GdbQBf GdcQjes - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj , J (B468 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HJaSjQ Chd ShQI GdCfYGe , (B[(3bhdg (B:(3W bhdg (B: (3GdMeO ddg bGd GHf YHGS (B: (3jQjO Ydi cd aYGd hHcd dSGf hYdi fYe GdESdGe s
(3BNQgG (B:s
(3jfJgi CKfGA JaSjQ bhdg JYGdi (B: (3fMf fbU Ydjc fHCge (B" (3ef ShQI Gdcga s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQg GdYGeI(B((3JaSjQ (B149) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs